1998
DOI: 10.1007/bf02486412
|View full text |Cite
|
Sign up to set email alerts
|

Size effect and fracture energy studies using compact compression specimens

Abstract: The size effect has been investigated and fracture energy, G F, determined for a range of different strength concretes. The test specimen geometry used in the study was a compact compression prism. Five sizes of geometrically similar specimens with increasing square crosssectional area (length = depth) and constant thickness (100 ram) were used in the experimental work; the length/depth dimensions of the test specimens were 100, 150, 200, 300, and 400 ram, giving an overall size range ratio of 1:4. The grades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The test presented in type I was commonly used to evaluate the fracture properties based on LEFM whereas type II was utilized to evaluate the fracture energy of concrete with medium and high strength values. 18 In previous studies on CCS, the values of K I were only determined because CCS was only used for LEFM-based analyses of concrete. It is also well-known that at least two fracture parameters that were determined experimentally are necessary to achieve modelling of a concrete structure by adopting principles of fracture mechanics.…”
Section: K Unmentioning
confidence: 99%
See 2 more Smart Citations
“…The test presented in type I was commonly used to evaluate the fracture properties based on LEFM whereas type II was utilized to evaluate the fracture energy of concrete with medium and high strength values. 18 In previous studies on CCS, the values of K I were only determined because CCS was only used for LEFM-based analyses of concrete. It is also well-known that at least two fracture parameters that were determined experimentally are necessary to achieve modelling of a concrete structure by adopting principles of fracture mechanics.…”
Section: K Unmentioning
confidence: 99%
“…compression specimens (CCS) were utilized in the determination of fracture parameters, which covered fracture toughness or critical strain energy release rate or fracture energy in cementitious material according to the fracture mechanics of Hookean materials. [12][13][14][15][16][17][18] As mentioned above, the proper simulation of a concrete structure, as well as the fracture toughness parameter, requires at least one more parameter in length dimension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the size effect curve yields information on the brittleness of the specimens but the work of fracture method does not. In the case of concretes, the size effect method was applied successfully to the failure of concrete structures failing in tension, in diagonal shear, in torsion [27,28], in pull-out of reinforcing bars [29], in bond splice [30], in compression [31,32,33,34], in bending [35,36,37] as well as by Arcan tests [38].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason the description of the behavior of concrete is incorrect in terms of plasticity, and thus a size effect is observed. Recent developments in fracture mechanics have shown that the size effects which are observed in the failure of concrete structures are due to the concrete rather than the steel; this is true not only when the concrete fails in tension, (diagonal shear, bar pull-out, torsion, etc), but also when the concrete fails in compression, except when there are confining pressures that greatly exceed the uniaxial compression strength [2][3][4] . Recent studies [5][6][7] have shown that by adding sufficient quantities of randomly distributed short fibers of appropriate geometries to the matricesit is possible to improve the behavior of plain concrete and conventionally reinforced concrete in terms of both ductility and residual strength, especially in the case of high strength concrete.…”
Section: Introductionmentioning
confidence: 99%